1983
DOI: 10.1016/s0010-9452(83)80007-0
|View full text |Cite
|
Sign up to set email alerts
|

CT scan Cerebral Hemispheric Asymmetry Measurements in Stroke Cases with Global Aphasia: Atypical Asymmetries Associated with Improved Recovery

Abstract: This study was undertaken in order to examine the relationship between CT scan hemispheric asymmetries and recovery in aphasia. The study had two parts. In Part I, hemispheric asymmetries were measured on the CT scans of 60 right-handed male non-aphasic (non-neurological) controls and 89 right-handed male aphasics, using a modification of LeMay's (1977) techniques. Both the non-aphasic control and aphasic data were in agreement with that of LeMay for frontal width, occipital width and occipital length. In Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…That various brain asymmetries have been correlated with handedness (LeMay 1976(LeMay , 1977LeMay and Kid0 1978;Bear et al 1986;Kertesz et al 19861, sex (Wada et al 1975;Bear et al 19861, recovery from aphasia (Pieniadz et al 1983) and hemiplegia (Scheckman et al 1983) following stroke, developmental dyslexia (Hier et al 1978b), schizophrenia (Luchins et al 19791, and autism (Hier et al 1978a) argues in favor of the basic premise that size asymmetries are behaviorally relevant. Angular, areal, and topological distortion are discussed in detail in Appendix 11.…”
Section: -Slice Linementioning
confidence: 99%
“…That various brain asymmetries have been correlated with handedness (LeMay 1976(LeMay , 1977LeMay and Kid0 1978;Bear et al 1986;Kertesz et al 19861, sex (Wada et al 1975;Bear et al 19861, recovery from aphasia (Pieniadz et al 1983) and hemiplegia (Scheckman et al 1983) following stroke, developmental dyslexia (Hier et al 1978b), schizophrenia (Luchins et al 19791, and autism (Hier et al 1978a) argues in favor of the basic premise that size asymmetries are behaviorally relevant. Angular, areal, and topological distortion are discussed in detail in Appendix 11.…”
Section: -Slice Linementioning
confidence: 99%
“…However, the evidence for such claims is rather limited [24,25]. Atypical skull asymmetries (large left frontal or right occipital torque) were associated with a better prognosis in one study [26], but this was not confirmed by subsequent investigations [27,28].…”
Section: Biographical Factors: Gender Handedness Education Agementioning
confidence: 99%
“…From a morphological point of view, hemisphere asymmetry has been described to have an effect on recovery from aphasia. 17 From a functional point of view, variations in plastic changes after damage to the brain should be regarded as a possible mechanism. The early occurrence and persistence of compensatory functions have been verified in animal studies.…”
Section: Discussionmentioning
confidence: 99%